The portrait of gender justice and injustice in the Islamic teaching text-book and Muhammadiyah teachersâ responses - Nurwanto, Nurwanto (State Institute of Islamic Studies (STAIN) Salatiga, 2013)
The paper investigates the textbook on Islamic teaching officially published forMuhammadiyah Senior Secondary Schools. It examines whether the textbookpromotes gender justice or injustice. In addition, how the teachers think aboutthe gender discourse is also explored. The study seems important to carry out bytaking account of whether the trend of gender discourses which has taken placefor some decades in the public is substantially accommodated in the Muhammadiyahschoolsâ curriculum. Moreover, the teachersâ responses to the existing genderissues as included in the textbook may be crucial to shape since they are transla-tors of the text offered. To clarify this issue, the paper uses content analysis ofthe textbook and analyses the result of interview with several Muhammadiyahsenior secondary schoolsâ teachers in Yogyakarta. The result of this study showsthat even if the content of the official textbook generally emphasizes genderjustice, in some cases, it promotes gender injustice and stereotypes. The expla-nation of menâs social roles in the whole Muslimsâ history tends to be widelyexplored whereas that of the possibility of womenâs roles is paid less attention.On the other hand, in other parts of the textbook, there is an explanation ofÂ the The paper investigates the textbook on Islamic teaching officially published forMuhammadiyah Senior Secondary Schools. It examines whether the textbookpromotes gender justice or injustice. In addition, how the teachers think aboutthe gender discourse is also explored. The study seems important to carry out bytaking account of whether the trend of gender discourses which has taken placefor some decades in the public is substantially accommodated in the Muhammadiyahschoolsâ curriculum. Moreover, the teachersâ responses to the existing genderissues as included in the textbook may be crucial to shape since they are transla-tors of the text offered. To clarify this issue, the paper uses content analysis ofthe textbook and analyses the result of interview with several Muhammadiyahsenior secondary schoolsâ teachers in Yogyakarta. The result of this study showsthat even if the content of the official textbook generally emphasizes genderjustice, in some cases, it promotes gender injustice and stereotypes. The expla-nation of menâs social roles in the whole Muslimsâ history tends to be widelyexplored whereas that of the possibility of womenâs roles is paid less attention.On the other hand, in other parts of the textbook, there is an explanation ofÂ theIJIMS, Indonesian Journal of Islam and Muslim Societies, Volume 3, Number 1, JuneÂ 2012: 149-173150importance of democratic attitudes for Muslims in the framework of societal re-lations. In the sense, the elaboration of the possibility of men and women toparticipate in the public is theologically explained. With regard to the teachersâresponses, the writing indicates that they generally agree with the notion of theneed for women and men to share and possibly contribute in the public as longas the women in particular do not deny their domestic roles. They seem trying toexamine the content of the textbook ranging from rational up to theological con-siderations. To conclude, the textbookÂ contains gender justice and injustice ori-entations which have been responded variously by the teachers.Kajian ini menelaah buku teks tentang ajaran Islam yang resmi diterbitkan untukSekolah Menengah Atas Muhammadiyah. Kajian ini menguji apakah buku tekstersebut mempromosikan keadilan atau ketidakadilan gender. Di samping itu,kajian ini mengeksplorasi bagaimana para guru berpikir mengenai wacana gen-der. Kajian ini penting untuk mempertimbangkan apakah kecenderungan wacanagender yang telah terjadi beberapa dekade ini secara substantif diakomodasioleh kurikulum sekolah-sekolah Muhammadiyah. Lebih jauh, respon para guruterhadap persoalan-persoalan gender yang ada sebagaimana termuat dalambuku teks menjadi penting karena mereka merupaka para penerjemah dari bukuteks tersebut. Untuk mencapai itu semua, kajian ini menggunakan analisis isiatas buku teks dan menelaah hasil wawancara dengan beberapa guru SekolahMenengah Atas Muhammadiyah di Yogyakarta. Hasil kajian ini menunjukkan bahwameskipun secara umum muatan buku teks resmi menekankan keadilan gender,dalam beberapa hal, juga mempromosikan ketidakadilan gender dan prasangka.PenjelasanÂ mengenaiÂ peranÂ sosialÂ lelakiÂ dalamÂ keseluruhanÂ sejarahÂ Muslimcenderung memperoleh paparan luas, sementara peran sosial perempuan kurangmemperoleh perhatian. Di sisi lain, sebagian buku teks juga menjelaskan tentangpentingnya sikap demokratis bagi Muslim dalam kerangka hubungan-hubungansosial. DalamÂ hal ini, elaborasi mengenai peluang lelaki dan perempuan untukberpartisipasiÂ dalamÂ ruangÂ publikÂ telahÂ dijelaskanÂ secaraÂ teologis.Â Denganmemperhatikan respon paraguru, kajian ini menunjukkan bahwa mereka umumnyasepakat dengan paham mengenai erlunya perempuan dan lelaki berbagi danmungkin berkontribusiÂ dalam ruang publik sejauh perempuan tidak menolakperan domestik mereka. Mereka agaknya mencoba menguji muatan buku teksmelalui pertimbangan rasional hingga teologis. Akhrinya, buku teks bermuatan orientasi keadilan ketidakadilan gender yang telah direspon secara berbeda olehpara guru.